'I don't think my torso is anything to write home about': men's reflexive production of 'authentic' photos for online dating platforms. - Waling, Andrea; Kehlher, Michael; Power, Jennifer; Kerr, Lucille; Bourne, Adam (Journal of Gender Studies, 2023)
This paper explores men's use of dating apps with an emergent body image focus, addressing cisgender, heterosexual men's feelings about dating app profile pictures. Drawing from interviews with 15 cisgender, heterosexual men residing in Australia about their use of dating applications including Tinder, Hinge, and Bumble, this paper examines how cisgender, heterosexual men construct their dating app profile pictures, and the decisions they make about the content of images they use for dating profile pictures. Utilizing concepts of self-presentation, authenticity, and bodily reflexive practices, this paper argues that the men in the study are attempting to present authentic and real selves in a dating world, while being confronted by concerns regarding body image and perceptions of ideal bodies. They also demonstrate conflicting desires to appear more muscular, fit, and athletic while not presenting as vain or narcissistic. In the process of creating profiles, these men develop a sense of self drawing on understandings of masculinity and specifically notions of idealized male bodies, which simultaneously run counter to the very authentic images of the self they seek to present.